Peran apoteker dalam edukasi resistensi antibiotik di Kecamatan Keruak Lombok Timur - Oktresia, Erma Ewisa; Gemantari, Baiq Maylinda; Yuliana, Tri Puspita; Ramadhan, Leny; Azim, Muhlisun (Universitas Mataram, 2024)
Pharmacists is one among others profession whom responsible to manage and to prevent antimicrobial resistance. To perform those function, giving information and educating public are essential to be done. This community service was aimed to provide and to increase knowledge and awareness of antimicrobial usage in public by educational program. Thus, the incidence of antimicrobial resistance could decline. The program was run by classical method and discussion session. There were 30 participants from various village in Keruak district. As speaker, pharmacists delivered some learning materials to participants followed by discussion. On discussion session participant asked some questions about antimicrobial usage. According to questions asked, it showed that participants taking part in this program have not comprehend about how to get, how to use, how to keep and storage and how to dispose antimicrobial yet in a frame to prevent resistance. It is concluded that by taking this educational community service program given by pharmacists, participants in Keruak district could gain information to improve their knowledge about antimicrobial usage in order to prevent and decline antimicrobial resistance.